Cell-type-specific nuclei purification from whole animals for genome-wide expression and chromatin profiling. - Steiner, F.A.; Talbert, P.B.; Kasinathan, S.; Deal, R.B.; Henikoff, S. (Genome Research, 2012)
An understanding of developmental processes requires knowledge of transcriptional and epigenetic landscapes at the level of tissues and ultimately individual cells. However, obtaining tissue- or cell-type-specific expression and chromatin profiles for animals has been challenging. Here we describe a method for purifying nuclei from specific cell types of animal models that allows simultaneous determination of both expression and chromatin profiles. The method is based on in vivo biotin-labeling of the nuclear envelope and subsequent affinity purification of nuclei. We describe the use of the method to isolate nuclei from muscle of adult Caenorhabditis elegans and from mesoderm of Drosophila melanogaster embryos. As a case study, we determined expression and nucleosome occupancy profiles for affinity-purified nuclei from C. elegans muscle. We identified hundreds of genes that are specifically expressed in muscle tissues and found that these genes are depleted of nucleosomes at promoters and gene bodies in muscle relative to other tissues. This method should be universally applicable to all model systems that allow transgenesis and will make it possible to determine epigenetic and expression profiles of different tissues and cell types.